Diabetes Medication Metformin Inhibits Osteoclast Formation and Activity in In Vitro Models for Periodontitis - Tao, Lucy Y.; Łagosz-Ćwik, Katarzyna B.; Hogervorst, Jolanda M.A.; Schoenmaker, Ton; Grabiec, Aleksander M.; Forouzanfar, Tim; van der Weijden, Fridus A.; de Vries, Teun J. (Frontiers in Cell and Developmental Biology, 2022)
Diabetes and periodontitis are comorbidities and may share common pathways. Several reports indicate that diabetes medication metformin may be beneficial for the periodontal status of periodontitis patients. Further research using appropriate cell systems of the periodontium, the tissue that surrounds teeth may reveal the possible mechanism. Periodontal ligament fibroblasts anchor teeth in bone and play a role in the onset of both alveolar bone formation and degradation, the latter by inducing osteoclast formation from adherent precursor cells. Therefore, a cell model including this type of cells is ideal to study the influence of metformin on both processes. We hypothesize that metformin will enhance bone formation, as described for osteoblasts, whereas the effects of metformin on osteoclast formation is yet undetermined. Periodontal ligament fibroblasts were cultured in the presence of osteogenic medium and 0.2 or 1 mM metformin. The influence of metformin on osteoclast formation was first studied in PDLF cultures supplemented with peripheral blood leukocytes, containing osteoclast precursors. Finally, the effect of metformin on osteoclast precursors was studied in cultures of CD14+ monocytes that were stimulated with M-CSF and receptor activator of Nf-κB ligand (RANKL). No effects of metformin were observed on osteogenesis: not on alkaline phosphatase activity, Alizarin red deposition, nor on the expression of osteogenic markers RUNX-2, Collagen I and Osteonectin. Metformin inhibited osteoclast formation and accordingly downregulated the genes involved in osteoclastogenesis genes: RANKL, macrophage colony stimulating factor (M-CSF) and osteoclast fusion gene DC-STAMP. Osteoclast formation on both plastic and bone as well as bone resorption was inhibited by metformin in M-CSF and RANKL stimulated monocyte cultures, probably by reduction of RANK expression. The present study unraveling the positive effect of metformin in periodontitis patients at the cellular level, indicates that metformin inhibits osteoclast formation and activity, both when orchestrated by periodontal ligament fibroblasts and in cytokine driven osteoclast formation assays. The results indicate that metformin could have a systemic beneficiary effect on bone by inhibiting osteoclast formation and activity.